Penyelenggaraan Makanan di Unit Gizi Rumah Sakit X Kabupaten Jember - Maulina, Alya Zah'ra (Pustaka Kesehatan, 2024)
Organization of hospital meals, namely an activity carried out by the hospital nutrition installation related to the provision of food for patients. Based on the data obtained, it is known that food waste at Hospital X Jember Regency is at a total average of 26.04%; this figure is not in accordance with the maximum standard of food waste, which is approximately 20%. This study aims to determine the implementation of food in the Nutrition Unit of Hospital X Jember Regency. This research is descriptive. The population of this study was 12 people, and we used a sample from a total population unit of 12 people (3 working in the nutrition office, 9 working in the kitchen). Data collection is done through interviews, observation, and documentation. The results showed that there were three parameters for storing food ingredients that were not in accordance with Permenkes Number 07 of 2019, namely that there were two drainages, namely under the wet food storage area (refrigerator) and under the warehouse door for dry food storage, and no samples of finished food samples in the refrigerator of the Nutrition Unit of RS X. It is recommended not to place wet food storage areas and dry food storage areas near drainage or waste water drains and to place finished food samples in food sample storage areas at any time to avoid something happening (disturbance) to patients and related complaints about food served to patients.